Assessing Emotional Intelligence as An Innovative Dimension in The Attainment of Quality Education: A Mauritian Insight - Panchoo Preeyamvada; Sajjad Shahida (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
This paper aims primarily to report the findings of the research project which attempted to explore the extent to which Emotional Intelligence (EI) influences the attainment of Quality Education (QE) within the public secondary educational setting in Mauritius. This paper is motivated by the fact that reason and emotions need to be aligned with a view of cultivating the integrated development of the powers of both the mind and the heart to ensure a sustainable education pathway. This study espoused an iterative approach to research design, subscribing to a mixed method while targeting a large population sample for generalisation of results. The perception of QE and EI were assessed through quantitative and qualitative data which were collected through survey questionnaires for educators and school leaders and discourses from regional directors following semi-structured interviews conducted. Analysis of results gathered from educators, school leaders and zone directors related to state-owned secondary schools indicated a positive impact of EI on QE in contemporary times.